PENGARUH PEMBERIAN HUKUMAN TERHADAP PRILAKU SISWA SMP NEGERI 2 BUKIT BATU BENGKALIS - Wirdafitri '; Zahirman '; Gimin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was based on student who violates the school rules. In this case the school must apply effective regulation to be used as guidelines or reference so that the rules were not violated by the student. Punishment applied by educators or teachers to students aimed to provide as a deterrent effect. According to Abu Ahmadi and Nur Uhbiyati (Ahmadi, 2001) punishment was an act, in which we consciously and deliberately dropped sorrow to others, both in bodily and in terms of spirituality because others have a weakness when compared to ourselves. This study aimed to determine whether there was influence between punishments given with the students’ behavior of SMP Negeri 2 Bukit Batu Bengkalis? The population of this study was all students of SMP Negeri 2 Bukit Batu Bengkalis. The sample was determined by using purposive sampling which students who get punishment as many as 51 people. Instrument data collection was questionnaire consisted of 25 the question of the students’ attitude before and after getting a punishment. Data analyzed using t test. Thus the hypothesis "There was Influence between punishments given with students’ behavior of SMP Negeri 2 Bukit Batu Bengkalis was accepted. This was proven by a series of t-test for comparing the behavior of the students before and after getting a punishment. From the calculation results obtained count = 10:29 and t table or t = 2.01 that can be seen that: t0 was greater than t 10:29> 2:01. because t0 was greater than the t then H0 rejected.Keywords: Giving Punishment, Student Behavior